Qualidade de vida de profissionais de saúde da linha de frente no pós pandemia da COVID-19 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The COVID-19 pandemic brought several impacts and difficulties to society, as well claims constant adaptations in the performance of health services, especially of hospitalized patients. Frontline healthcare workers faced work overload, physical and psychological symptoms due to the rapid increase in hospital admissions, as well as intense pressures and demands. This study aims to investigate the impact on quality of life that the action in the front line mobilized in health professionals. First, through a systematic review, a search for scientific productions that corroborated the performance of health professionals during the pandemic against quality of life was conducted. Was searched in the ScienceDirect, Scopus and Scielo database using the following descriptors: Quality of life AND COVID-19 AND Healthcare Workers. Was founded 51 articles in the databases, in which after reading in full, 39 articles were selected for analysis. The publications founded are located on all continents, in which the various cultural contexts were influential in conducting the fight against the virus. It was identified that doctors, nurses, assistants and physiotherapists were the most studied health professionals, in which female health professionals were the most affected due to the performance in the front line. Anxiety, bournout and depression were the most prevalent pathologies in the subjects surveyed, not being evident how these symptoms were managed for care during the period of action. Subsequently, 25 semi-structured interviews were conducted with health professionals who make up a multidisciplinary team, starting from five reference questions. The interviews were recorded, transcribed in full and analyzed in the light of the content analysis proposed by Bardin (2011). From the data collection emerged five thematic categories, being described as "I no longer had a life outside the hospital", "That constant fear of losing people", "So today I still deal with anxiety", "Calm sea never made good sailor" and "We give much more value to life". It is identified that the greatest feelings and thoughts mobilized in the participants were fear of death, perceptions of exacerbated anxiety, learning from the performance, work overload and resilience over personal and professional life. It is concluded that there is an important impact on the quality of life of health professionals in relation to their actions in the COVID-19 pandemic, however, these impacts were possible to be resignified leaving the pole of losses for learning and teaching.
Keywords: COVID-19; Profissionais de Saúde; Qualidade de Vida; COVID-19; Healthcare Workers; Quality of life; CNPQ::CIENCIAS DA SAUDE